Patient Profile and Survival Rate of Breast Cancer Patients with FEC Chemotherapy Regimen at H. Adam Malik Hospital - Alfi Syahri G; Retno Murwanti; Agung Endro Nugroho (Jurnal Sains dan Kesehatan, 2023)
Breast cancer is a prevalent disease that impacts public health worldwide, including Indonesia. There are various chemotherapy regimens that are currently available. One widely utilized chemotherapy regimen for breast cancer is the FEC regimen, which combines 5-fluorouracil, epirubicin, and cyclophosphamide. This study provides a study of patient profiles and survival rates among breast cancer patients undergoing FEC chemotherapy at H. Adam Malik Hospital. The study utilized a descriptive-retrospective approach with data collected from the medical records of patients who underwent FEC therapy at RSUP H. Adam Malik during January-December 2019. A total of 157 patients were administered anthracycline-based treatment, with 54 patients receiving FEC (34.39%). The majority of individuals under the FEC regimen were primarily luminal B (51.75%) and IBC (33.33%). The survival rate for individuals using the FEC chemotherapy regimen was found to be 37.98 months. Additionally, patients with risk factors associated with invasive breast cancer (IBC) exhibited a 1.20-fold increased risk of mortality compared to individuals with other forms of breast cancer. The first-line FEC chemotherapy regimen continues to be a feasible therapeutic option for subtypes of breast cancer, and there is no discernible variation in survival rate observed across these characteristics.